Intraocular pressure measurement and association with corneal biomechanics in patients underwent Descemet’s stripping with endothelial keratoplasty: a comparative study - Chen, Huiyu; Wu, Suqian; Tian, Lijia; Li, Yue; Hong, Jiaxu; Wang, Yulan; Xu, Jianjiang (Frontiers in Medicine, 2024)
Purpose. To compare corneal biomechanical properties and intraocular pressure (IOP) measurements in patients who underwent Descemet's stripping with endothelial keratoplasty (DSEK) with those of the follow healthy eyes.Methods. In this retrospective comparative study, a total of 35 eyes of 35 patients who underwent DSEK by a single surgeon from 2015.02 to 2019.12 were enrolled along with their fellow healthy eyes. Corneal biomechanical parameters were assessed at least 3 months post-DSEK using Corneal Visualization Scheimpflug Technology (CST). IOP was measured by CST, Goldmann applanation tonometry (GAT), and MacKay-Marg tonometer.Results. Central corneal thickness (CCT) and stiffness parameter at first applanation (SP-A1) were significantly increased after DSEK when compared to the fellow eyes. In DSEK eyes, biomechanically-corrected intraocular pressure (bIOP) and MacKay-Marg IOP correlated significantly with GAT IOP measurements, with bIOP showed the lowest IOP values. All the IOP values did not correlate with CCT. However, GAT-IOP and MacKay-Marg IOP showed a positive correlation with SP-A1.The corneal stiffness increased after DSEK. Central corneal thickness may have less influence than corneal biomechanics on IOP measurements in eyes after DSEK. Biomechanicallycorrected IOP obtained by CST seemed to be lower than other tonometry techniques in DSEK eyes, perhaps because of correction for corneal stiffness, CCT and age.